2016
DOI: 10.5125/jkaoms.2016.42.5.271
|View full text |Cite
|
Sign up to set email alerts
|

Diseases having an influence on inhibition of angiogenesis as risk factors of osteonecrosis of the jaw

Abstract: ObjectivesThe objective of this study was to retrospectively investigate the association of diseases having an influence on inhibition of angiogenesis such as hypertension, diabetes mellitus type II, hypercholesterolemia, and rheumatoid arthritis (RA) with the development of osteonecrosis of the jaws.Materials and MethodsThe 135 patients were allocated into 4 groups of bisphosphonate-related osteonecrosis of the jaw (BRONJ) group (1A); non-BRONJ group (1B); osteonecrosis of the jaw (ONJ) group (2A); and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Low peripheral VEGF levels have been previously associated with MRONJ 43 , 62 . In human studies, serum VEGF and TGF-β levels were reported to be significantly suppressed after administration of intravenous bisphosphonate, suggesting that peripheral VEGF and inflammatory marker levels could represent a possible predictive marker for susceptibility to MRONJ 43 , 63 .…”
Section: Discussionmentioning
confidence: 96%
“…Low peripheral VEGF levels have been previously associated with MRONJ 43 , 62 . In human studies, serum VEGF and TGF-β levels were reported to be significantly suppressed after administration of intravenous bisphosphonate, suggesting that peripheral VEGF and inflammatory marker levels could represent a possible predictive marker for susceptibility to MRONJ 43 , 63 .…”
Section: Discussionmentioning
confidence: 96%
“…Paek et al. [66] reported that the effects of diabetes and hypertension were not statistically significant for the development of BRONJ. When not considering BP use, RA exhibited a high odds ratio of 3.23 (P = 0.094) for development of ONJ [66] .…”
Section: Risk Factors For Aronjmentioning
confidence: 99%
“…Planning personalised periodic follow-up appointments they must be investigated during an examination [2,[40][41][42][43][44].…”
Section: Primary Prevention In Patients Who Are Prescribed Onj-relate...mentioning
confidence: 99%